EPIDEMIOLOGICAL INVESTIGATION DIPTHERIA CASES IN KEDIRI DISTRICT IN 2022 - Nofita Sari (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2023)
Background: Diphtheria is a type of infectious disease that can be prevented by immunization. The cause of diphtheria is the toxigenic strain of Corynebacterium diphtheriae. East Java is the province with the most diphtheria cases in Indonesia. The number of diphtheria cases in East Java increased in 2018 by 695 cases. In 2019 diphtheria cases decreased to 358 cases, in 2020 to 94 cases, and in 2021 by 45 cases. Objective: Knowing the number of diphtheria cases and their prevention. Method: descriptive qualitative research with a case study approach. The definition of a case is a person with symptoms of fever, sore throat, swelling in the neck, and pseudomembranes. Data collection was conducted in five villages, namely Keling Village, Kanigoro Village, Kras Village, Jemekan Village, and Bogem Village in the period from October to November 2022. Results: Clinical symptoms, 100% or all five patients experienced symptoms of fever and sore throat as initial symptoms. Four patients had a fever as the initial symptom, and one started with a sore throat. 40% of patients had symptoms of neck swelling and shortness of breath. The five patients were also found to have pseudomembranes. Conclusion: There were 5 diphtheria suspects found in Kediri District in 2022. The clinical symptoms experienced by the five patients were fever, sore throat, neck swelling, shortness of breath, and pseudomembranes.